Accurate Detection of Non-Cavitated Proximal Caries in Posterior Permanent Teeth: An in vivo Study - Alammar R; Sadaf D (Dove Medical Press, 2020)
Raghad Alammar,1 Durre Sadaf2,3 1Qassim University, College of Dentistry, Buraidah, Alqassim, Saudi Arabia; 2Conservative Dentistry Department, Qassim University, College of Dentistry, Buraidah, Alqassim, Saudi Arabia; 3University of Oxford, Centre for Evidence-Based Medicine, Nuffield Department of Primary Care Health Sciences, Oxford, UKCorrespondence: Raghad Alammar Tel +966 583573888Email RaghadAalammar@gmail.comPurpose: This study aimed to compare the sensitivity and specificity of DIAGNOdent versus bitewing radiographs in detecting non-cavitated proximal caries.Patients and Methods: This observational prospective study included 120 proximal surfaces, without obvious cavitation, on permanent mandibular and maxillary posterior teeth in patients over 16 years old. The DIAGNOdent test was performed, and digital bitewing radiographs were obtained; these were compared with a standard reference method, which comprised a clinical assessment of the proximal surfaces following the application of an orthodontic separator between the teeth for 7 days. Each test was performed by a different investigator blinded to the assessment results of the other examiners.Results: The DIAGNOdent device exhibited a higher sensitivity in detecting enamel proximal caries (95%) than digital bitewing radiographs (64%), and the specificity of DIAGNOdent (89%) was greater than that of bitewing radiographs (77%). Regarding the detection of dentin caries, the sensitivities of DIAGNOdent and bitewing radiographs were similar (both 62%); however, the specificity of DIAGNOdent was higher (98% versus 88%). The results of the Kruskal–Wallis test revealed a significant difference in DIAGNOdent scores across the three diagnoses (sound tooth surfaces, enamel caries, dentin caries) (p-value < 0.001).Conclusion: The diagnostic accuracy of DIAGNOdent in detecting enamel caries is significantly higher than that of digital bitewing radiography. The routine use of DIAGNOdent can facilitate an accurate diagnosis of early carious lesions and inform the implementation of preventive treatment.Keywords: bitewing, dental caries, dentition, permanent, radiography